The Role Of Innovation In Mediating The Effect Of Market Orientation And Learning Orientation On Competitive Advantage - Berty Christina Lidyanita Putri; Putu Yudi Setiawan (Journal of Business and Management Review, 2022)
In Denpasar City, the growth of small culinary businesses has resulted in increased competition. Because this growth does not correspond to an increase in turnover, today's small businesses must innovate to gain a competitive advantage and win market share to thrive in the future. The purpose of this study is to determine the impact of market orientation and learning orientation on competitive advantage, as well as the impact of innovation on competitive advantage and the impact of mediating innovation on the relationship between market orientation and competitive advantage and the relationship between learning orientation and competitive advantage. Two exogenous variables, market orientation, and learning orientation, and two endogenous variables, innovation, and competitive advantage, are used in this study. The population in this study was a small culinary business that has been operating in Denpasar City for at least three years. A total of 166 small businesses were included in this study's sample. Purposive sampling was used as the sampling method. A questionnaire was used to collect information. SEM-PLS analysis with SmartPLS 3.0 was used to analyze the data. The results of the analysis showed that market orientation had a significant effect on competitive advantage and innovation. Likewise, learning orientation also had a significant effect on competitive advantage and innovation. A significant effect was also found on the relationship between innovation and competitive advantage. On the other hand, innovation did not mediate the relationship between market orientation and competitive advantage, but innovation partially mediated the relationship between learning orientation and competitive advantage. The implications of the research are expected to be used as reference material for further research with the basic theory of resourced based view oriented to the company's internal strengths, while the practical implications are expected to be additional information or references for small business actors in implementing market orientation and learning orientation which is the focus in developing innovation. to achieve a competitive advantage.